Methane synthesis catalyst and its preparation method and application
By using a combination of modified silica support and active components, the problems of low activity, poor selectivity and stability of traditional catalysts under low temperature gas-liquid solid three-phase conditions are solved, and the high level in the slurry bed reactor is achieved Stability and good activity.
Patent Information
- Application Number
- CN202111187742.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-10-12
AI Technical Summary
The prior art Under the low-temperature gas-liquid solid three-phase conditions, traditional methane synthesis catalysts have low activity, poor selectivity and stability, making it difficult to effectively use in slurry bed reactors.
The modified silica support and the active components supported thereon are used to prepare the catalyst by ball milling-kneading method to improve the binding degree and structure-activity relationship between the active components and the support, and enhance the stability and activity of the catalyst.
Under the gas-liquid solid three-phase conditions of the slurry bed, the catalyst exhibits high stability, good activity and selectivity, and can maintain the selectivity of methane at more than 90.5% after 300 hours, and the conversion rate of carbon monoxide at 92.3% after 300 hours. above.
Smart Images

Figure BDA0003299968400000111 
Figure BDA0003299968400000112 
Figure BDA0003299968400000241
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysis, and in particular relates to a slurry bed methane synthesis catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, the environmental carrying capacity has been weakening, and the environmental protection pressure has gradually increased. As a clean and efficient energy source, the demand for natural gas has surged. As a major coal-producing country, my country can use coal-to-gas technology to not only achieve clean and efficient use of coal, but also make up for the shortage of natural gas in my country.
[0003] The core of coal-to-natural gas technology is methane synthesis technology. Methanation reaction is a highly exothermic reaction. At present, industrial methanation reactions mostly adopt the form of multiple fixed bed reactors in series. The heat generated in the process is removed by multiple heat exchangers. In order to dilute the gas concentration at the inlet of the reactor to an appropriate range, a circulating compressor needs to be added. The process is relatively complicated. If it is not well controlled, it is very easy to cause the reactor to overheat. This puts forward very high requirements on the high temperature resistance and carbon deposition resistance of the methane synthesis catalyst. As a system that uses an inert liquid with high thermal conductivity as a medium to diffuse the reaction heat in time so that its reaction process is close to a constant temperature, the slurry bed reactor can effectively avoid problems such as high-temperature sintering or carbon deposition of the catalyst in the fixed bed reactor. However, the reaction temperature of the slurry bed reactor is relatively low and it is carried out in an inert liquid. When the fixed bed methane synthesis catalyst is used in the slurry bed reactor, it will have problems such as poor low-temperature activity and poor stability under the gas-liquid-solid three-phase conditions of the slurry bed, and cannot be used well in it. Therefore, it is urgent to develop a slurry bed methane synthesis catalyst with good activity and high stability at low temperatures.
[0004] CN106563455A discloses a Fe / Co / Ni-Cu based slurry bed methanation catalyst, whose carrier is prepared by a sol-gel method or a co-precipitation method. Under the conditions of a reaction temperature of 200-300°C and a reaction pressure of 0.1-8.0MPa, the catalyst has a high CH4 selectivity of 67.5-94.3%; but its CO conversion rate is low, only 31.8-88.4%.
[0005] CN103801304A discloses a reduction-free slurry bed methanation catalyst, which adopts a solution combustion method to prepare a Ni / Al2O3 catalyst. Under the conditions of a reaction temperature of 250-350°C and a reaction pressure of 1.0-4.0MPa in an inert liquid phase composed of paraffin hydrocarbons, heat transfer oil, hydrogenated terphenyl, etc., the CO conversion rate is greater than 90.6%, and the CH4 selectivity is greater than 91.4%. However, the data is obtained after a certain reaction time and there is no indication, so the stability of the catalyst cannot be verified. In addition, since this method must be carried out under high temperature combustion, it is easy to cause the growth, agglomeration, and uneven burning of grains, which makes it difficult to achieve large-scale industrial production.
[0006] CN107029726A discloses a Ni / SiO2-based slurry bed methanation catalyst, which has a CO conversion rate of 90-97% and a CH4 selectivity of 91-94% under the conditions of 300-330°C and 1.0-3.0MPa, but the stability of the catalyst is not mentioned.
[0007] CN105688919A discloses a Ni / Al2O3 slurry bed methanation catalyst prepared by a precipitation combustion method, with a CO conversion rate of 90.3-96.4% and a CH4 selectivity of 89.3-93.4%, but the stability of the catalyst is not mentioned.
[0008] At present, in terms of slurry bed methane synthesis catalysts, how to prepare catalysts that have high low-temperature activity, good selectivity, and long-term reaction stability under gas-liquid-solid three-phase conditions is an important issue that researchers need to solve. Summary of the invention
[0009] The purpose of the present invention is to overcome the problems of low activity, poor selectivity and stability of traditional methane synthesis catalysts under gas-liquid-solid three-phase conditions with low reaction temperature in the prior art, and to provide a slurry bed methane synthesis catalyst and its preparation method and application, as well as a slurry bed method for preparing methane. The methane synthesis catalyst of the present invention has high stability under gas-liquid-solid three-phase conditions, high binding degree between its active components and carriers, and good structure-activity relationship; and the preparation process is simple, reproducible, and easy to promote industrialization. It has good activity, selectivity and stability when used in a slurry bed reactor.
[0010] In order to achieve the above object, the first aspect of the present invention provides a slurry bed methane synthesis catalyst, wherein the catalyst comprises a modified silica carrier and an active component supported on the modified silica carrier;
[0011] Wherein, the specific surface area of the modified silica carrier is 270-340m 2 / g, average pore diameter of 60-130nm, pore volume of 0.6-1cm3 / g.
[0012] A second aspect of the present invention provides a method for preparing a slurry bed methane synthesis catalyst, comprising the following steps:
[0013] (1) mixing a carrier precursor with activated carbon and performing ball milling to obtain a modified silica carrier precursor;
[0014] (2) contacting the modified silica carrier precursor with a binder and kneading them, extruding and drying them after the kneading is uniform, to obtain a modified silica carrier;
[0015] (3) impregnating the modified silica support in a solution containing an active component precursor, and then drying and calcining the solution in sequence to obtain a catalyst precursor;
[0016] (4) crushing the catalyst precursor, sieving it, and then reducing it to obtain a slurry bed methane synthesis catalyst;
[0017] Wherein, the carrier precursor is a mixture of mesoporous silica and pretreated diatomaceous earth.
[0018] The third aspect of the present invention provides a slurry bed methane synthesis catalyst prepared by the above preparation method.
[0019] A fourth aspect of the present invention provides use of the above catalyst in slurry bed methane synthesis.
[0020] A fifth aspect of the present invention provides a method for preparing methane in a slurry bed, the method comprising: in a slurry bed reactor, in the presence of hydrogen and a catalyst, carrying out a methane synthesis reaction using carbon monoxide as a raw material, wherein the catalyst is the above-mentioned catalyst.
[0021] Through the above technical solution, the present invention has the following beneficial effects:
[0022] 1) The slurry bed methane synthesis catalyst of the present invention uses a modified silica carrier, and the specific surface area of the modified silica carrier is 270-340m 2 / g, average pore diameter of 60-130nm, pore volume of 0.6-1cm 3 / g, which can firmly combine the active components with the carrier to form a stable framework, and make the catalyst still have high stability under the gas-liquid-solid three-phase conditions of the slurry bed;
[0023] 2) The specific surface area of the catalyst of the present invention is 180-250m 2 / g, average pore diameter of 45-100nm, pore volume of 0.45-0.9cm 3 / g, so that the catalyst still has high activity, selectivity and stability under low reaction temperature and gas-liquid-solid three-phase conditions;
[0024] 3) The modified silica carrier of the present invention contains 2.78-6.25 wt% of activated carbon, 0.8-1.8 wt% of Al2O3, 0.2-0.6 wt% of Fe2O3, 0.1-0.3 wt% of MgO, 0.1-0.4 wt% of CaO, and 0.08-0.15 wt% of K2O (Al2O3, Fe2O3, MgO, CaO, and K2O are derived from natural diatomaceous earth), so that the interaction between the carrier and the active components is significantly enhanced, and the catalyst has good stability. At the same time, the oxides of Al, Fe, Mg, Ca, and K also play the role of additives, thereby improving the activity of the catalyst, so that the selectivity for methane is still above 90.5% after the reaction for 300 hours, and the conversion rate of carbon monoxide is still above 92.3%;
[0025] 4) The present invention adopts a ball milling-kneading method to mix activated carbon, mesoporous silica and diatomaceous earth for ball milling. The obtained modified silica carrier has good specific surface area, pore volume and pore size. When used as a carrier of a slurry bed methane synthesis catalyst, it has the advantages of high bonding degree between the active component and the carrier, stable framework structure and improved catalyst activity;
[0026] 5) The catalyst preparation method of the present invention has simple process, good reproducibility and is easy to promote industrially. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] The first aspect of the present invention provides a slurry bed methane synthesis catalyst, characterized in that the catalyst comprises a modified silica carrier and an active component supported on the modified silica carrier;
[0029] Wherein, the specific surface area of the modified silica carrier is 270-340m 2 / g, average pore diameter of 60-130nm, pore volume of 0.6-1cm 3 / g. The inventors found in their research that when the modified silica carrier has the above-mentioned specific surface area, average pore diameter and pore volume parameters, the active component is firmly combined with the carrier to form a stable framework, and the catalyst after loading the active component has a suitable specific surface area, average pore diameter and pore volume.
[0030] In some embodiments of the present invention, based on the total weight of the catalyst, the content of the modified silica carrier is 82-92 wt %; based on the oxide of the active component, the content of the active component is 8-18 wt %.
[0031] In some embodiments of the present invention, the active component is nickel. Preferably, based on the total weight of the catalyst, the content of the modified silica carrier is 82-92 wt %; based on nickel oxide, the content of nickel is 8-18 wt %.
[0032] In the present invention, the chemical formula of the nickel oxide is NiO.
[0033] In some embodiments of the present invention, the modified silica carrier contains at least one of activated carbon, Al2O3, Fe2O3, MgO, CaO, and K2O. The inventors found that when the modified silica carrier contains the above components, the above components have the effect of an auxiliary agent, which can further enhance the catalytic activity of the active components. Preferably, based on the weight of the modified silica carrier, the activated carbon content is 2.78-6.25% by weight, the Al2O3 content is 0.8-1.8% by weight, the Fe2O3 content is 0.2-0.6% by weight, the MgO content is 0.1-0.3% by weight, the CaO content is 0.1-0.4% by weight, the K2O content is 0.08-0.15% by weight, and the silica content is 91.5-94.34% by weight. In the present invention, the impurity content in the modified silica is negligible.
[0034] In some embodiments of the present invention, the specific surface area of the catalyst is 180-250m 2 / g, average pore diameter of 45-100nm, pore volume of 0.45-0.9cm 3 / g.
[0035] A second aspect of the present invention provides a method for preparing a slurry bed methane synthesis catalyst, comprising the following steps:
[0036] (1) mixing a carrier precursor with activated carbon and performing ball milling to obtain a modified silica carrier precursor;
[0037] (2) contacting the modified silica carrier precursor with a binder and kneading them, extruding them into strips after kneading them evenly, and first drying them to obtain a modified silica carrier;
[0038] (3) impregnating the modified silica support in a solution containing an active component precursor, and then sequentially performing a second drying and calcining to obtain a catalyst precursor;
[0039] (4) crushing the catalyst precursor, sieving it, and then reducing it to obtain a slurry bed methane synthesis catalyst;
[0040] Wherein, the carrier precursor is a mixture of mesoporous silica and pretreated diatomaceous earth.
[0041] The inventors found in their research that a modified silica carrier obtained by ball-milling mesoporous silica, pretreated diatomaceous earth and activated carbon has a specific surface area, pore size and pore volume suitable for use as a carrier for methane synthesis reaction in a slurry bed, and the modified silica carrier can more firmly bind to the active component when loading the active component.
[0042] In the present invention, in order to further reduce the influence of impurities in diatomaceous earth on the performance of the final catalyst, and also to retain components such as Al, Fe, Mg, Ca, K in diatomaceous earth, the synergistic effect of their oxides (such as Al2O3, Fe2O3, MgO, CaO, K2O) on the catalytic activity of the active components of the catalyst in the final catalyst is utilized, and no other impurities are introduced, and pretreated diatomaceous earth is used in the method.
[0043] In some embodiments of the present invention, the pretreatment method is: after the diatomaceous earth is treated with acid, it is washed and dried for the fourth time. In the present invention, the content of silicon dioxide in the pretreated diatomaceous earth is 80-97% by weight (based on the weight of the pretreated diatomaceous earth). Preferably, the acid treatment is acid treatment using dilute nitric acid. The method and conditions for the acid treatment described in the present invention are conventionally selected in the art, for example, the diatomaceous earth can be immersed in 1-4% by weight dilute nitric acid for 1-5h at room temperature. In the present invention, the method and conditions for washing and the fourth drying are conventionally selected in the art. Preferably, the washing is washed until the pH value of the eluate is 7-7.5. Preferably, the content of silicon dioxide in the pretreated diatomaceous earth described in the present invention is 90.66-96.72% by weight.
[0044] In the present invention, the "room temperature" refers to 20-30°C.
[0045] In some embodiments of the present invention, in step (1), the specific surface area of the activated carbon is 500-1000m 2 When the specific surface area and pore size of the activated carbon are within the above ranges, the prepared modified silica carrier has pores and specific surface area suitable for use as a carrier for methane synthesis reaction in a slurry bed.
[0046] In some embodiments of the present invention, in order to prepare a modified silica carrier with suitable pores, the pore size of the mesoporous silica is 2-50 nm.
[0047] In some embodiments of the present invention, in order to enable the small-pore mesoporous silica and the large-pore diatomaceous earth to form a solid carrier framework, thereby improving the mechanical strength of the modified silica carrier obtained and improving the stability of the catalyst finally obtained, the mass ratio of the mesoporous silica to the diatomaceous earth is 1:2-5. It should be noted that the mass of the diatomaceous earth here is the mass of the diatomaceous earth without pretreatment. When the mass ratio of the mesoporous silica to the diatomaceous earth exceeds the above range, the activity and stability of the obtained catalyst will be reduced.
[0048] In the present invention, the activated carbon can enhance the binding ability of the active component with the prepared modified silica carrier. In some embodiments of the present invention, in order to further enhance the binding ability of the active component with the modified silica carrier, the mass ratio of the activated carbon to the carrier precursor is 1:15.5-37.
[0049] In the present invention, the drying may be a drying method commonly used in the art, for example, drying in a drying oven.
[0050] In the present invention, the specific operation method and conditions of kneading can be the methods and conditions commonly used in the art, as long as sufficient kneading can be achieved.
[0051] In the present invention, the specific operation method and conditions of the ball milling can be conventionally selected in the art. In some embodiments of the present invention, in order to shorten the industrial production time and to fully mix the activated carbon with diatomaceous earth and mesoporous silica, the ball milling is carried out in a ball mill, and the ball milling conditions are: a rotation speed of 320-480 rpm and a time of 1-3 h.
[0052] In some embodiments of the present invention, the method further comprises performing a third drying on the activated carbon, and the temperature of the third drying is 120-180°C.
[0053] In the present invention, the reduced mass of the activated carbon after the third drying is negligible.
[0054] In some embodiments of the present invention, the binder is at least one of citric acid, sesbania powder, and cellulose.
[0055] In some embodiments of the present invention, the amount of the binder is 3-8 wt % based on the weight of the modified silica support precursor.
[0056] In the present invention, the weight of the modified silica carrier precursor is the sum of the weights of the carrier precursor and the activated carbon, and the loss during mixing and ball milling is negligible.
[0057] In some embodiments of the present invention, in step (2), the first drying temperature is 100-120° C., and the first drying time is 2-4 hours.
[0058] And / or, the immersion treatment temperature is 40-70° C., and the immersion treatment time is 0.5-1.5 h.
[0059] In some embodiments of the present invention, in step (3), the second drying is performed at a temperature of 100-120° C. for a time of 2-3 h.
[0060] In some embodiments of the present invention, in step (3), the calcination temperature is 350-450° C. and the calcination time is 3-4 h.
[0061] In some embodiments of the present invention, the modified silica carrier and active component precursor are used in such amounts that, in the prepared catalyst, the content of the carrier is 82-92 wt % based on the total weight of the catalyst, and the content of the active component is 8-18 wt % based on the oxide of the active component.
[0062] In some embodiments of the present invention, the active component precursor is a nickel component precursor.
[0063] In some embodiments of the present invention, the modified silica carrier and the nickel component precursor are used in such amounts that, in the prepared catalyst, the carrier content is 82-92 wt % based on the total weight of the catalyst, and the nickel content is 8-18 wt % calculated as nickel oxide.
[0064] In some embodiments of the present invention, in step (3), the active component precursor is a soluble nickel salt, preferably nickel nitrate hexahydrate (Ni(NO3)2·6H2O).
[0065] In some embodiments of the present invention, the concentration of the solution containing the active component precursor is 0.12-0.25 g / ml, calculated as the oxide of the active component. When the concentration of the active component precursor solution is within the above range, the active component can be completely absorbed by the carrier after one impregnation, saving industrial production steps and reducing production costs. In addition, the catalyst activity obtained by combining the active component with the oxides of Al, Fe, Mg, Ca, K, etc. in the modified silica carrier meets the requirements of slurry bed methane synthesis.
[0066] In the present invention, in step (3), after the second drying and calcination, a catalyst precursor containing a modified silica carrier and an oxide of an active component is obtained.
[0067] In the present invention, in step (4), the catalyst precursor is crushed, sieved and then reduced, so that the oxide of the active component in the catalyst precursor is converted into an active component, and the catalyst of the present invention is obtained. In the present invention, in step (4), the method and conditions for reduction after crushing and sieving are conventionally selected in the art and are not repeated here. Preferably, the reduction comprises: reducing the catalyst precursor in a fixed bed reactor under a hydrogen atmosphere, and the hydrogen atmosphere can be a hydrogen gas containing 20-100v%, preferably 100v% hydrogen. Preferably, the catalyst precursor is crushed, sieved and taken to 100-120 mesh.
[0068] In the present invention, in step (4), the catalyst precursor can be reduced immediately after the catalyst precursor is prepared, or before use (i.e., before use in methane synthesis). Since the active component is easily oxidized, it is preferred that the catalyst precursor be reduced in step (4) before slurry bed methane synthesis for ease of transportation and storage.
[0069] According to a particularly preferred embodiment of the present invention, the method for preparing the slurry bed methane synthesis catalyst comprises the following steps:
[0070] 1) Place 50-100g of activated carbon in a drying oven at 120-180°C and dry to constant weight;
[0071] 2) Pre-treating diatomaceous earth: taking 970-1750 g of diatomaceous earth, treating it with 1-4 wt % dilute nitric acid, washing it with distilled water until the pH value is 7.0-7.5, and drying it to obtain pre-treated diatomaceous earth (based on the weight of the pre-treated diatomaceous earth, the content of silicon dioxide is 80-97 wt %), and setting it aside;
[0072] 3) adding the pretreated diatomaceous earth, 250-600 g of mesoporous silica and activated carbon into a ball mill and milling for 1-3 h to obtain a modified silica carrier precursor, wherein the mass ratio of mesoporous silica to diatomaceous earth is 1:(2-5), and the mass ratio of activated carbon to (the sum of mesoporous silica and pretreated diatomaceous earth) is 1:(15.5-37);
[0073] 4) Based on the weight of the modified silica carrier precursor, 3-8 wt% of a binder and the modified silica carrier precursor are added into a kneader for kneading, and after kneading evenly, the mixture is extruded and dried to obtain a modified silica carrier;
[0074] 5) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.12-0.25 g / mL (based on nickel oxide);
[0075] 6) Control the temperature of the impregnation solution at 40-70°C and immerse an equal volume of the carrier in the impregnation solution for 0.5-1.5 hours;
[0076] 7) taking out the impregnated catalyst precursor, drying at 100-120°C, and calcining at 350-450°C to obtain the catalyst precursor;
[0077] 8) The catalyst precursor is crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced under a hydrogen atmosphere to obtain a slurry bed methane synthesis catalyst, wherein the nickel loading is 8-18% by weight based on the total weight of the slurry bed methane synthesis catalyst in terms of nickel oxide.
[0078] The third aspect of the present invention provides a slurry bed methane synthesis catalyst prepared by the above preparation method.
[0079] A fourth aspect of the present invention provides an application of the above-mentioned slurry bed methane synthesis catalyst in slurry bed methane synthesis.
[0080] A fifth aspect of the present invention provides a method for slurry bed methane synthesis, the method comprising: in a slurry bed reactor, in the presence of hydrogen and a catalyst, carrying out a methane synthesis reaction using carbon monoxide as a raw material, wherein the catalyst is the above-mentioned slurry bed methane synthesis catalyst.
[0081] In some embodiments of the present invention, the molar ratio of the amount of hydrogen to carbon monoxide is 1:3-4;
[0082] The present invention uses the catalyst provided above. Preferably, the reaction conditions are: paraffin as the liquid phase component, stirring speed 1000-1500r / min, temperature 260-340°C, pressure 1.0-3.0MPa, space velocity 1500-5000h -1 .
[0083] In some embodiments of the present invention, in order to allow the catalyst to fully contact with the reaction gas in the gas-liquid-solid three-phase slurry bed and eliminate the influence of internal diffusion, the size of the slurry bed methane synthesis catalyst is 100-120 mesh.
[0084] The present invention will be described in detail below by way of examples. It should be understood that the following examples are only used to further explain and illustrate the content of the present invention by way of example, and are not intended to limit the present invention.
[0085] In the following examples, unless otherwise specified, all reagents and raw materials used are commercially available, and the methods used are conventional methods in the art and will not be described in detail herein.
[0086] Mesoporous silica has a pore size of 2-50nm;
[0087] The specific surface area of activated carbon is 500-1000m 2 / g, pore size is 10-60nm;
[0088] Diatomite was purchased from Yunnan Diatomite Products Factory with the brand name YX04;
[0089] The nickel content in the catalyst is calculated as nickel oxide, and the nickel oxide content is determined by atomic absorption spectroscopy.
[0090] The contents of activated carbon, Al2O3, Fe2O3, MgO, CaO and K2O in the modified silica carrier were determined by atomic absorption spectroscopy, and the silica content was determined by high-temperature ashing weight loss method.
[0091] The specific surface area, pore volume and pore size of the modified silica support were measured by BET.
[0092] The specific surface area, pore volume and pore size of the catalyst were measured by BET.
[0093] The composition and content of the reaction product were detected by Agilent 8890 gas chromatograph.
[0094]
[0095]
[0096] Example 1
[0097] 1) Dry 50 g of activated carbon in a drying oven at 140°C until constant weight is used;
[0098] Pre-treat diatomite: take 1200 g of diatomite, treat it with 3 wt% dilute nitric acid (immerse the diatomite in dilute nitric acid for 3 h at room temperature), wash it with distilled water until the pH value is 7.2, and then dry it for later use. The content of silicon dioxide in the pre-treated diatomite is 91.48 wt%;
[0099] The pretreated diatomaceous earth, 600 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:37) are added together in a ball mill and ball milled for 1 h (at a speed of 480 rpm) to obtain a modified silica carrier precursor;
[0100] 2) adding 60 g of citric acid and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 110° C. for 2 h to obtain a modified silica carrier 1;
[0101] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.12 g / mL (based on nickel oxide);
[0102] The temperature of the impregnation liquid is controlled at 60° C., and an equal volume of the modified silicon dioxide obtained in step (2) is immersed in the impregnation liquid for 1.5 h to obtain a catalyst precursor;
[0103] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 110° C. for 3 h and calcined at 400° C. for 3 h to obtain the catalyst precursor;
[0104] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain a slurry bed methane synthesis catalyst I (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount in terms of nickel oxide is 8 wt %, and the rest is a silica carrier).
[0105] In the modified silica carrier 1, based on the weight of the modified silica carrier 1, the content of activated carbon is 3.98 wt%, the content of Al2O3 is 0.8 wt%, the content of Fe2O3 is 0.4 wt%, the content of MgO is 0.1 wt%, the content of CaO is 0.4 wt%, the content of K2O is 0.08 wt%, the content of silica is 94.24 wt%, and the specific surface area is 270 m 2 / g, average pore diameter of 130nm, pore volume of 1.0cm 3 / g.
[0106] The specific surface area of slurry bed methane synthesis catalyst I is 180m 2 / g, average pore diameter is 100nm, pore volume is 0.9cm 3 / g.
[0107] Example 2
[0108] 1) Place 100 g of activated carbon in a drying oven at 180°C and dry to constant weight for later use;
[0109] Pre-treat diatomite: take 1500g diatomite, treat it with 3 wt% dilute nitric acid (immerse the diatomite in dilute nitric acid for 4h at room temperature), wash it with distilled water until the pH value is 7.2, and then dry it for use. The content of silicon dioxide in the pre-treated diatomite is 93.61 wt%;
[0110] The pretreated diatomaceous earth, 300 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:18.6) are added together in a ball mill and ball milled for 3 h (at a speed of 320 rpm) to obtain a modified silica carrier precursor;
[0111] 2) adding 76 g of sesbania powder and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 120° C. for 2 h to obtain a modified silica carrier 2;
[0112] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.2 g / ml (calculated as nickel oxide);
[0113] The temperature of the impregnation solution was controlled at 60° C., and an equal volume of the modified silica support was immersed in the impregnation solution for 1.0 h to obtain a catalyst precursor;
[0114] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 120° C. for 3 h and calcined at 450° C. for 4 h to obtain the catalyst precursor;
[0115] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain a slurry bed methane synthesis catalyst II (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount is 14% by weight calculated as nickel oxide, and the rest is a modified silica carrier).
[0116] The modified silica carrier 2 has an activated carbon content of 5.72 wt%, an Al2O3 content of 1.8 wt%, a Fe2O3 content of 0.3 wt%, a MgO content of 0.2 wt%, a CaO content of 0.4 wt%, a K2O content of 0.08 wt%, a silica content of 91.50 wt%, and a specific surface area of 300 m 2 / g, average pore diameter is 100nm, pore volume is 0.8cm 3 / g.
[0117] The specific surface area of slurry bed methane synthesis catalyst II is 220m 2 / g, average pore diameter of 75nm, pore volume of 0.8cm 3 / g.
[0118] Example 3
[0119] 1) Dry 75 g of activated carbon in a drying oven at 150°C to constant weight for later use;
[0120] Pre-treat diatomite: take 1350 g of diatomite, treat it with 2 wt% dilute nitric acid (immerse the diatomite in dilute nitric acid for 2 h at room temperature), wash it with distilled water until the pH value is 7.5, and then dry it for later use. The content of silicon dioxide in the pre-treated diatomite is 96.47 wt%;
[0121] The pretreated diatomaceous earth, 270 g of mesoporous silica, and dried activated carbon (the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:22) are added together into a ball mill and ball-milled for 2 h (at a speed of 400 rpm) to obtain a modified silica carrier precursor;
[0122] 2) adding 50 g of citric acid and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 110° C. for 3 h to obtain a modified silica carrier 3;
[0123] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.18 g / ml (based on nickel oxide);
[0124] The temperature of the impregnation liquid was controlled at 70° C., and an equal volume of the modified silica support obtained in step (2) was immersed in the impregnation liquid for 1.5 h to obtain a catalyst precursor;
[0125] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 120° C. for 2 h and calcined at 400° C. for 4 h to obtain the catalyst precursor;
[0126] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain a slurry bed methane synthesis catalyst III (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount is 12% by weight calculated as nickel oxide, and the rest is a silica carrier).
[0127] In the modified silica carrier 3, based on the weight of the modified silica carrier 3, the content of activated carbon is 4.92 wt%, the content of Al2O3 is 0.8 wt%, the content of Fe2O3 is 0.2 wt%, the content of MgO is 0.1 wt%, the content of CaO is 0.1 wt%, the content of K2O is 0.08 wt%, and the content of silica is 93.80 wt%. The specific surface area is 340 m 2 / g, average pore diameter is 60nm, pore volume is 0.6cm 3 / g.
[0128] The specific surface area of slurry bed methane synthesis catalyst III is 250m 2 / g, average pore diameter of 45nm, pore volume of 0.45cm 3 / g.
[0129] Example 4
[0130] 1) Dry 75 g of activated carbon in a drying oven at 150°C to constant weight for later use;
[0131] Pre-treat diatomite: take 1200 g of diatomite, treat it with 1 wt% dilute nitric acid (immerse the diatomite in dilute nitric acid for 5 h at room temperature), wash it with distilled water until the pH value is 7.0, and then dry it for later use. The content of silicon dioxide in the pre-treated diatomite is 90.66 wt%;
[0132] The pretreated diatomaceous earth, 600 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:24) are added together in a ball mill and ball milled for 2 h (at a speed of 350 rpm) to obtain a modified silica carrier precursor;
[0133] 2) adding 80 g of cellulose and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 120° C. for 2 h to obtain a modified silica carrier 4;
[0134] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.22 g / ml (based on nickel oxide);
[0135] The temperature of the impregnation solution was controlled at 60°C, and an equal volume of the support was immersed in the impregnation solution for 1.0 h to obtain a catalyst precursor;
[0136] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 110° C. for 2 h and calcined at 350° C. for 4 h to obtain the catalyst precursor;
[0137] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain a slurry bed methane synthesis catalyst IV (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount is 16% by weight calculated as nickel oxide, and the rest is a modified silica carrier).
[0138] In the modified silica carrier 4, based on the weight of the modified silica carrier 4, the content of activated carbon is 4.76 wt%, the content of Al2O3 is 1.5 wt%, the content of Fe2O3 is 0.4 wt%, the content of MgO is 0.2 wt%, the content of CaO is 0.3 wt%, the content of K2O is 0.1 wt%, the content of silica is 92.74 wt%, and the specific surface area is 280 m 2 / g, average pore diameter of 120nm, pore volume of 0.9cm 3 / g.
[0139] The specific surface area of slurry bed methane synthesis catalyst IV is 190m 2 / g, average pore diameter of 80nm, pore volume of 0.8cm 3 / g.
[0140] Example 5
[0141] 1) Dry 75 g of activated carbon in a drying oven at 150°C to constant weight for later use;
[0142] Pre-treat diatomite: take 1750 g of diatomite, treat it with 1 wt% dilute nitric acid (immerse the diatomite in dilute nitric acid for 5 h at room temperature), wash it with distilled water until the pH value is 7.2, and then dry it for later use. The content of silicon dioxide in the pre-treated diatomite is 96.68 wt%;
[0143] The pretreated diatomaceous earth, 350 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:29) are added together in a ball mill and ball milled for 2 h (at a speed of 450 rpm) to obtain a modified silica carrier precursor;
[0144] 2) adding 50 g of sesbania powder, 57 g of cellulose and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 110° C. for 3 h to obtain a modified silica carrier 5;
[0145] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.25 g / ml (based on nickel oxide metal);
[0146] The temperature of the impregnation liquid was controlled at 60° C., and an equal volume of the modified silica support obtained in step (2) was immersed in the impregnation liquid for 1.5 h to obtain a catalyst precursor;
[0147] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 120° C. for 2 h and calcined at 450° C. for 4 h to obtain the catalyst precursor;
[0148] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and after reduction at 450° C. for 5 h, a slurry bed methane synthesis catalyst V was obtained (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount was 18 wt % calculated as nickel oxide, and the rest was modified silica support).
[0149] The modified silica carrier 5 has an activated carbon content of 2.78 wt%, an Al2O3 content of 1.8 wt%, a Fe2O3 content of 0.6 wt%, a MgO content of 0.3 wt%, a CaO content of 0.4 wt%, a K2O content of 0.15 wt%, a silica content of 93.97 wt%, and a specific surface area of 330 m 2 / g, average pore diameter of 70nm, pore volume of 0.7cm 3 / g.
[0150] The specific surface area of slurry bed methane synthesis catalyst V is 230m 2 / g, average pore diameter of 55nm, pore volume of 0.5cm 3 / g.
[0151] Example 6
[0152] 1) Dry 50 g of activated carbon in a drying oven at 150°C to constant weight for later use;
[0153] Pre-treating the diatomite: taking 1500 g of diatomite, treating it with 3 wt % dilute nitric acid (immersing the diatomite in dilute nitric acid at room temperature for 2 h), washing it with distilled water until the pH value is 7.0, and drying it to obtain pre-treated diatomite for later use. The content of silicon dioxide in the pre-treated diatomite is 96.72 wt %;
[0154] The pretreated diatomaceous earth, 300 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:37) are added together in a ball mill and ball milled for 2 h (at a speed of 320 rpm) to obtain a modified silica carrier precursor;
[0155] 2) adding 56 g of citric acid and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 100° C. for 4 h to obtain a modified silica carrier 6;
[0156] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.12 g / mL (based on nickel oxide);
[0157] The temperature of the impregnation solution was controlled at 40° C., and an equal volume of the modified silica support was immersed in the impregnation solution for 0.5 h to obtain a catalyst precursor;
[0158] The catalyst precursor was taken out, and the catalyst precursor was dried at 120° C. for 2 h and calcined at 400° C. for 3 h to obtain the catalyst precursor;
[0159] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain a slurry bed methane synthesis catalyst VI (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount calculated as nickel oxide is 8 wt %, and the rest is a modified silica carrier).
[0160] The modified silica carrier 6 has an activated carbon content of 4.02 wt%, an Al2O3 content of 1.3 wt%, a Fe2O3 content of 0.4 wt%, a MgO content of 0.1 wt%, a CaO content of 0.1 wt%, a K2O content of 0.08 wt%, a silica content of 94.0 wt%, and a specific surface area of 275 m 2 / g, average pore diameter of 110nm, pore volume of 0.8cm 3 / g.
[0161] The specific surface area of slurry bed methane synthesis catalyst VI is 200m 2 / g, average pore diameter of 80nm, pore volume of 0.6cm 3 / g.
[0162] Example 7
[0163] 1) Dry 100 g of activated carbon in a drying oven at 160°C until constant weight is used;
[0164] Pre-treat diatomite: take 1250g diatomite, treat it with 4 wt% dilute nitric acid (immerse the diatomite in dilute nitric acid at room temperature for 2h), wash it with distilled water until the pH value is 7.5, and then dry it for later use. The content of silicon dioxide in the pre-treated diatomite is 93.73 wt%;
[0165] The pretreated diatomaceous earth, 250 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:15.5) are added together in a ball mill and ball milled for 3 h (at a speed of 420 rpm) to obtain a modified silica carrier precursor;
[0166] 2) adding 128 g of sesbania powder and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 120° C. for 2 h to obtain a modified silica carrier 7;
[0167] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.15 g / ml (based on nickel oxide);
[0168] The temperature of the impregnation solution was controlled at 70°C, and an equal volume of the support was immersed in the impregnation solution for 1.5 hours to obtain a catalyst precursor;
[0169] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 110° C. for 2 h and calcined at 400° C. for 3 h to obtain the catalyst precursor;
[0170] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain a slurry bed methane synthesis catalyst VII (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount in terms of nickel oxide is 10% by weight, and the rest is a modified silica carrier).
[0171] In the modified silica carrier 7, based on the weight of the modified silica carrier 7, the content of activated carbon is 6.25 wt%, the content of Al2O3 is 1.2 wt%, the content of Fe2O3 is 0.4 wt%, the content of MgO is 0.2 wt%, the content of CaO is 0.2 wt%, the content of K2O is 0.15 wt%, the content of silica is 91.60 wt%, and the specific surface area is 320 m 2 / g, average pore diameter of 80nm, pore volume of 0.7cm 3 / g.
[0172] The specific surface area of slurry bed methane synthesis catalyst VII is 230m 2 / g, average pore diameter of 70nm, pore volume of 0.5cm 3 / g.
[0173] Example 8
[0174] 1) Dry 50 g of activated carbon in a 180°C drying oven to constant weight for later use;
[0175] Pre-treat diatomite: take 970g diatomite, treat it with 2 wt% dilute nitric acid (immerse the diatomite in dilute nitric acid at room temperature for 4h), wash it with distilled water until the pH value is 7.1, and then dry it for later use. The content of silicon dioxide in the pre-treated diatomite is 96.29 wt%;
[0176] The pretreated diatomaceous earth, 325 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:26.7) are added together in a ball mill and ball milled for 1.5 h (at a speed of 380 rpm) to obtain a modified silica carrier precursor;
[0177] 2) adding 70 g of sesbania powder and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 100° C. for 3 h to obtain a modified silica carrier 8;
[0178] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.2 g / ml (calculated as nickel oxide);
[0179] The temperature of the impregnation liquid was controlled at 60° C., and an equal volume of the modified silica support obtained in step (2) was immersed in the impregnation liquid for 1.5 h to obtain a catalyst precursor;
[0180] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 100° C. for 2 h and calcined at 400° C. for 4 h to obtain the catalyst precursor;
[0181] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain slurry bed methane synthesis catalyst VIII (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount calculated as nickel oxide is 14% by weight, and the rest is silica carrier).
[0182] The modified silica carrier 8 has an activated carbon content of 4.41 wt%, an Al2O3 content of 0.8 wt%, a Fe2O3 content of 0.2 wt%, a MgO content of 0.1 wt%, a CaO content of 0.1 wt%, a K2O content of 0.08 wt%, a silica content of 94.31 wt%, and a specific surface area of 330 m 2 / g, average pore diameter of 70nm, pore volume of 0.6cm 3 / g.
[0183] The specific surface area of slurry bed methane synthesis catalyst VIII is 240m 2 / g, average pore diameter of 55nm, pore volume of 0.45cm 3 / g.
[0184] Example 9
[0185] 1) Dry 50 g of activated carbon in a drying oven at 150°C to constant weight for later use;
[0186] Pre-treat diatomite: take 1200g diatomite, treat it with 2% dilute nitric acid (immerse the diatomite in dilute nitric acid for 3h at room temperature °C), wash it with distilled water until the pH value is 7.2, and then dry it for use. The content of silicon dioxide in the pre-treated diatomite is 95.61% by weight;
[0187] The pretreated diatomaceous earth, 400 g of mesoporous silica, and dried activated carbon (wherein the mass ratio of activated carbon to (the sum of the pretreated diatomaceous earth and mesoporous silica) is about 1:33) are added together in a ball mill and ball milled for 3 h (at a speed of 480 rpm) to obtain a modified silica carrier precursor;
[0188] 2) adding 70 g of citric acid, 15 g of cellulose and the modified silica carrier precursor obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 120° C. for 2 h to obtain a modified silica carrier 9;
[0189] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.2 g / ml (calculated as nickel oxide);
[0190] The temperature of the impregnation liquid is controlled at 60° C., and an equal volume of the modified silica support obtained in step (2) is immersed in the impregnation liquid for 1.0 h to obtain a catalyst precursor;
[0191] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 120° C. for 2 h and calcined at 400° C. for 4 h to obtain the catalyst precursor;
[0192] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 , and reduced at 450° C. for 5 h to obtain a slurry bed methane synthesis catalyst IX (based on the total weight of the slurry bed methane synthesis catalyst, the nickel loading amount calculated as nickel oxide is 14% by weight, and the rest is a silica carrier).
[0193] In the modified silica carrier 9, based on the weight of the modified silica carrier 9, the content of activated carbon is 4.32 wt%, the content of Al2O3 is 1.1 wt%, the content of Fe2O3 is 0.3 wt%, the content of MgO is 0.2 wt%, the content of CaO is 0.2 wt%, the content of K2O is 0.1 wt%, the content of silica is 93.78 wt%, and the specific surface area is 325 m 2 / g, average pore diameter of 70nm, pore volume of 0.65cm 3 / g.
[0194] The specific surface area of slurry bed methane synthesis catalyst IX is 230m 2 / g, average pore diameter of 50nm, pore volume of 0.5cm 3 / g.
[0195] Comparative Example 1
[0196] (1) 500 g of mesoporous silica and 40 g of sesbania powder were kneaded together to form strips, which were then dried at 120° C. for 4 h and calcined at 400° C. for 3 h to obtain a carrier;
[0197] (2) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.2 g / ml (based on nickel oxide);
[0198] The temperature of the impregnation liquid was controlled at 60° C., and the support was immersed in the impregnation liquid for 1 hour to obtain a catalyst precursor;
[0199] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 120° C. for 2 h and calcined at 450° C. for 3 h to obtain the catalyst precursor;
[0200] 3) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 After reduction at 450°C for 5 hours, a comparative catalyst A was obtained in which the nickel loading amount was 12 wt% in terms of nickel oxide based on the total weight of the catalyst.
[0201] The specific surface area of the carrier obtained in step (1) is 480 m 2 / g, average pore diameter of 45nm, pore volume of 0.45cm 3 / g.
[0202] The specific surface area of comparative catalyst A is 390 m 2 / g, average pore diameter is 38nm, pore volume is 0.39cm 3 / g.
[0203] Comparative Example 2
[0204] 1) Dry 50 g of activated carbon in a 120°C drying oven to constant weight for later use;
[0205] 1000 g of mesoporous silica was added into a ball mill and ball-milled for 1 h (at a rotation speed of 400 rpm) to obtain a mixture;
[0206] 2) adding 80 g of sesbania powder and the mixture obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 110° C. for 3 h to obtain a carrier;
[0207] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.2 g / ml (calculated as nickel oxide);
[0208] The temperature of the impregnation liquid was controlled at 60° C., and an equal volume of the carrier obtained in step (2) was immersed in the impregnation liquid for 1.5 h to obtain a catalyst precursor;
[0209] The impregnated catalyst precursor was taken out, and the catalyst precursor was dried at 120° C. for 2 h and calcined at 450° C. for 3 h to obtain the catalyst precursor;
[0210] 4) The catalyst precursor was crushed and sieved to obtain 100-120 mesh in a fixed bed reactor and reduced by 100v% hydrogen at a space velocity of 1000h -1 After reduction at 450°C for 5 hours, a comparative catalyst B was obtained in which the nickel loading was 14 wt% in terms of nickel oxide based on the total weight of the catalyst and the rest was the carrier.
[0211] The specific surface area of the carrier obtained in step (2) is 475 m 2 / g, average pore diameter of 50nm, pore volume of 0.45cm 3 / g.
[0212] The specific surface area of comparative catalyst B is 370 m 2 / g, average pore diameter of 40nm, pore volume of 0.4cm 3 / g.
[0213] Comparative Example 3
[0214] 1) 50 g of activated carbon was placed in a drying oven at 180° C. and dried to constant weight, and added together with 1000 g of diatomaceous earth (without pretreatment) and ball-milled in a ball mill for 1.5 h (at a rotation speed of 350 rpm) to obtain a mixture;
[0215] 2) adding 70 g of cellulose and the mixture obtained in step (1) into a kneader for kneading, kneading evenly, extruding into strips, and drying at 120° C. for 3 h to obtain a carrier;
[0216] 3) Dissolve Ni(NO3)2·6H2O in water to prepare an impregnation solution with a concentration of 0.2 g / ml (calculated as nickel oxide);
[0217] The temperature of the impregnation solution was controlled at 60°C, and an equal volume of the support was immersed in the impregnation solution for 1.5 hours to obtain a catalyst precursor;
[0218] The impregnated catalyst precursor was taken out, and the catalyst was dried at 100°C for 3h and calcined at 400°C for 4h to obtain the catalyst precursor;
[0219] 4) The catalyst precursor was crushed, sieved to 100-120 mesh, loaded into a fixed bed reactor, and reduced by 100v% hydrogen at a space velocity of 1000h -1 After reduction at 450°C for 5 hours, a comparative catalyst C was obtained in which the nickel loading was 14 wt% in terms of nickel oxide based on the total weight of the catalyst and the rest was the carrier.
[0220] Based on the weight of the carrier obtained in step (2), the carrier obtained in step (2) has an activated carbon content of 6.25 wt%, an Al2O3 content of 1.8 wt%, a Fe2O3 content of 0.5 wt%, a MgO content of 0.2 wt%, a CaO content of 0.3 wt%, a K2O content of 0.12 wt%, a silica content of 90.83 wt%, and a specific surface area of 200 m 2 / g, average pore diameter of 110nm, pore volume of 0.9cm 3 / g.
[0221] The surface area of comparative catalyst C is 140 m 2 / g, average pore diameter is 90nm, pore volume is 0.78cm 3 / g.
[0222] Test Case
[0223] This test example is used to illustrate a method for preparing methane in a slurry bed using the slurry bed methane synthesis catalyst of the present invention.
[0224] 3 mL of catalysts I-IX and comparative catalysts AC were weighed with a measuring cylinder and loaded into a slurry bed reactor respectively. The stirring speed was 1100 r / min, the temperature was 320 °C, the pressure was 2.5 MPa, and the space velocity was 2000 h -1 , 600mL paraffin was used as the liquid medium, and the reaction was carried out under the condition of H2 / CO (volume ratio) = 3. Sampling and analysis were performed at 50h and 300h. The analysis results are shown in Table 1.
[0225] Table 1
[0226]
[0227]
[0228] It can be seen from Table 1 that the catalysts I-IX prepared by the present method showed good CO conversion rate and CH4 selectivity after 50h and 300h, although there was a slight decrease in varying degrees, the amplitude was very small; while the comparative catalysts AC showed good CO conversion rate and CH4 selectivity at 50h, but their reaction conversion rate and selectivity decreased to varying degrees after a 300h stability test, proving that these catalysts have poor stability in long-term operation under slurry bed conditions.
[0229] It can be seen from the examples and comparative examples that the modified silica carrier prepared by the method described in the present invention has a suitable specific surface area, average pore size and pore volume, and the catalyst finally prepared has a suitable specific surface area, average pore size and pore volume, and is suitable as a slurry bed methane synthesis catalyst.
[0230] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A slurry bed methane synthesis catalyst, characterized in that: The catalyst comprises a modified silica carrier and an active component supported on the modified silica carrier; Wherein, the active component is nickel; Wherein, the specific surface area of the modified silica carrier is 270-340m 2 / g, average pore diameter of 60-130nm, pore volume of 0.6-1cm 3 / g; Based on the total weight of the catalyst, the content of the modified silica carrier is 82-92% by weight, and the content of nickel in terms of nickel oxide is 8-18% by weight; Based on the weight of the modified silica carrier, the activated carbon content is 2.78-6.25% by weight, the Al2O3 content is 0.8-1.8% by weight, the Fe2O3 content is 0.2-0.6% by weight, the MgO content is 0.1-0.3% by weight, the CaO content is 0.1-0.4% by weight, the K2O content is 0.08-0.15% by weight, and the silica content is 91.5-94.34% by weight.
2. The slurry bed methane synthesis catalyst according to claim 1, wherein: The specific surface area of the catalyst is 180-250m 2 / g, average pore diameter of 45-100nm, pore volume of 0.45-0.9cm 3 / g.
3. A method for preparing a slurry bed methane synthesis catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) mixing the carrier precursor with activated carbon and performing ball milling to obtain a modified silica carrier precursor; (2) contacting the modified silica carrier precursor with a binder and kneading them, extruding them into strips after kneading them evenly, and first drying them to obtain a modified silica carrier; (3) impregnating the modified silica support in a solution containing an active component precursor, and then performing a second drying and calcining in sequence to obtain a catalyst precursor; (4) crushing and sieving the catalyst precursor and then reducing it to obtain a slurry bed methane synthesis catalyst; Wherein, the carrier precursor is a mixture of mesoporous silica and pretreated diatomaceous earth; The pretreatment method is: treating the diatomaceous earth with acid, washing it, and drying it; The mass ratio of the mesoporous silica to the untreated diatomaceous earth is 1:2-5; The mass ratio of the activated carbon to the carrier precursor is 1:15.5-37; The binder is at least one of citric acid, sesbania powder and cellulose; The modified silica carrier and active component precursor are used in such amounts that, in the prepared catalyst, the carrier content is 82-92% by weight, based on the total weight of the catalyst, and the nickel content is 8-18% by weight, calculated as nickel oxide.
4. The preparation method according to claim 3, wherein The acid used in the acid treatment is dilute nitric acid.
5. The preparation method according to claim 3 or 4, wherein In step (1), the specific surface area of the activated carbon is 500-1000m 2 / g, pore size is 10-60nm.
6. The preparation method according to claim 3 or 4, wherein: The pore size of the mesoporous silica is 2-50 nm.
7. The preparation method according to claim 3 or 4, wherein: The ball milling conditions are: rotation speed of 320-480 rpm, and time of 1-3 h.
8. The preparation method according to claim 3 or 4, wherein: In step (1), the method further comprises performing a third drying on the activated carbon, wherein the temperature of the third drying is 120-180°C.
9. The preparation method according to claim 3 or 4, wherein: In step (2), the amount of the binder used is 3-8% by weight based on the weight of the modified silica carrier precursor.
10. The preparation method according to claim 3 or 4, wherein: In step (2), the first drying temperature is 100-120° C., and the first drying time is 2-4 hours.
11. The preparation method according to claim 3 or 4, wherein: In step (3), the second drying temperature is 100-120°C and the time is 2-3 hours.
12. The preparation method according to claim 3 or 4, wherein: The calcination temperature is 350-450° C. and the calcination time is 3-4 hours.
13. The preparation method according to claim 3 or 4, wherein: The active component precursor is a soluble nickel salt.
14. The preparation method according to claim 13, wherein: The active component precursor is nickel nitrate.
15. The preparation method according to claim 14, wherein: The active component precursor is nickel nitrate hydrate.
16. The preparation method according to claim 14, wherein: The active component precursor is nickel nitrate hexahydrate.
17. The preparation method according to claim 3 or 4, wherein: The immersion treatment temperature is 40-70° C., and the immersion treatment time is 0.5-1.5 h.
18. The preparation method according to claim 3 or 4, wherein: Calculated as nickel oxide, the concentration of the solution containing the active component precursor is 0.12-0.25 g / mL.
19. A slurry bed methane synthesis catalyst prepared by the preparation method according to any one of claims 3 to 18.
20. Use of the catalyst according to any one of claims 1 to 2 and 19 in slurry bed methane synthesis.
Citation Information
Patent Citations
Reduction-free methanation catalyst for slurry reactor as well as preparation method and application thereof
CN103801304A
Slurry reactor nickel-based methanation catalyst prepared according to sediment burning method and application thereof
CN105688919A
Cu-based catalyst for preparing CH4 through Co hydrogenation on slurry bed and preparing method and application
CN106563455A
Preparation method and application of nanometer nickel-based CO methanation catalyst
CN107029726A
Method for preparing X substituted 1-naphthylamine from X substituted 1-nitronaphthalene
CN101475489A